The Impossible Anastomosis: Intima-to-adventitia Suture Technique for Microanastomosis of Severely Calcified Arteries - Cai, Aijia; Horch, Raymund E.; Arkudas, Andreas (Plastic and Reconstructive Surgery Global Open, 2021)
Microsurgery in patients with advanced atherosclerosis is challenging. Calcified vessels can hinder microanastomosis, which precludes free flap reconstruction in those patients. We present a case of a female patient with stage 4 peripheral artery disease who had undergone mastectomy because of invasive breast cancer. During autologous breast reconstruction with a muscle-sparing transverse rectus abdominis free flap, we experienced difficulties during microanastomosis due to complicated plaques in an extremely calcified inferior epigastric artery. Also, the intima presented completely detached from the media, leading to a collapse of the vessel lumen. To prevent curling of the intima and prolapse of the atherosclerotic plaques into the vessel lumen, the intima was sutured to the adventitia by interrupted stitches. This maneuver led to eversion of the intima and facilitated the otherwise unfeasible anastomosis. The reconstructed breast showed adequate perfusion during the postoperative course. We present a technique to facilitate microanastomosis in severely calcified and fragile arteries.
CRIS-Team WoS Importer:2021-10-29